Pengaruh Cash Ratio (CR), Total Asset Turnover (TATO), Return On Assets (ROA) Terhadap Dividend Payout Ratio (DPR) Pada Perusahaan Sektor Aneka Industri dan Industri Barang Konsumsi yang Terdapat di Bursa Efek Indonesia Tahun 2013-2017 - Lindi Lindi; Yulia Paramitha; Hera Eria Br Sitepu; Sri Devi Erawati Tampubolon; Wenny Anggeresia Ginting; Mohd. Nawi Purba (Jurnal Ilmiah ESAI, 2019)
This study aims to determine the effect of Cash Ratio, Total Asset Turnover and Return On Assets on Dividend Payout Ratio in the Various Industries and Consumer Goods Industry found on the Indonesian Stock Exchange. The populations of this study were all companies in the various goods industries and consumer goods industry in the Indonesia Stock Exchange of 85 companies in the period 2013-2017. The technique of determining the sample used is purposive sampling. The samples obtained are 23 companies incorporated in the various goods industry and consumer goods industry sectors in the Indonesia Stock Exchange for the period 2013-2017. The data analysis technique used is the classic assumption test and multiple linear regression analysis with the help of SPSS 20. Based on the analysis, the results show that Cash Ratio and Total Asset Turnover have no significant effect on Dividend Payout Ratio, while Influential Return On Assets gives positive and significant effect on the Dividend Payout Ratio.Keywords : Cash Ratio, Total Asset Turnover, Sales, Return On Assets, Dividend Payout Ratio